Twenty Years After: Armenian Research Libraries Today - Aram Donabedian, D.; Carey, John; Balayan, Arshak (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2012)
Since achieving statehood in 1991, Armenia has faced major economic and political obstacles which have significantly affected the nation’s research libraries. This research paper will quantitatively and qualitatively examine the challenges facing Armenian research libraries just over twenty years after the collapse of the Soviet Union. Specifically, the authors analyze their interviews with five library administrators at five major institutions, respectively. These include Yerevan State University Library, the National Library of Armenia, the Fundamental Scientific Library of the National Academy of Sciences of Armenia, the Republican Scientific-Medical Library of Armenia, and the Papazian Library of the American University of Armenia. The instrument for the interviews consists of 73 questions based on the 2004 Association of College and Research Libraries Standards for Libraries in Higher Education and evaluates the following factors: • The library’s mission, goals and objectives • Public or user services • Instruction activities at the library • Resources (print, media, or electronic) and collection development • Access to the library’s resources • Outcome assessment, or evaluation of the library • Staffing issues • Facility maintenance and plans for library development • Communication and cooperation both within the library and with the user community • Administration • Budget In addition, we will focus on the strengths and weaknesses of these libraries and investigate the growing open access movement in Armenia. Based on our findings, the authors wish to facilitate dialogue and consider possible approaches to help these libraries meet Armenia’s pressing information needs.